2010
DOI: 10.1161/circulationaha.110.936674
|View full text |Cite
|
Sign up to set email alerts
|

Preeclampsia and Gestational Hypertension Are Associated With Childhood Blood Pressure Independently of Family Adiposity Measures

Abstract: Background Offspring of women with hypertensive disorders of pregnancy are at increased risk of cardiovascular complications later in life, but the mechanisms underlying these associations are unclear. Our aim was to examine whether adjusting for birthweight and familial adiposity changed the association of hypertensive disorders of pregnancy with offspring blood pressure. Methods and Results Using data from 6,343 nine-year-old participants of the Avon Longitudinal Study of Parents and Children, we examined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
173
6
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 191 publications
(197 citation statements)
references
References 30 publications
(38 reference statements)
16
173
6
2
Order By: Relevance
“…A large Finnish study suggested that offspring born after preeclampsia may be at higher risk of stroke later in life but found no association with coronary heart disease. [10][11][12][22][23][24][25][26] In a systematic review, including >45 000 participants, Davis et al 12 reported positive associations of preeclampsia with offspring blood pressure (systolic and diastolic) and BMI that were similar to ours. It has also been suggested that the higher childhood blood pressure associated with maternal hypertension in pregnancy may Values are shown as mean differences (95% CI) compared with offspring born after a normotensive pregnancy.…”
Section: Discussionsupporting
confidence: 80%
“…A large Finnish study suggested that offspring born after preeclampsia may be at higher risk of stroke later in life but found no association with coronary heart disease. [10][11][12][22][23][24][25][26] In a systematic review, including >45 000 participants, Davis et al 12 reported positive associations of preeclampsia with offspring blood pressure (systolic and diastolic) and BMI that were similar to ours. It has also been suggested that the higher childhood blood pressure associated with maternal hypertension in pregnancy may Values are shown as mean differences (95% CI) compared with offspring born after a normotensive pregnancy.…”
Section: Discussionsupporting
confidence: 80%
“…The observed effects were also not mediated by pregnancy complications, birth characteristics, or infant growth, which are all identified risk factors related to both maternal prepregnancy BMI and health of offspring. [38][39][40][41] Thus, our findings suggest that associations of maternal prepregnancy BMI with offspring cardiometabolic health outcomes may, at least partly, be explained by direct intrauterine mechanisms. This may include higher maternal plasma concentrations and placental transfer of glucose, amino acids, and free fatty acids during pregnancy, which may influence programming of offspring adiposity and an adverse cardiometabolic profile in later life.…”
Section: Interpretation Of Main Findingsmentioning
confidence: 63%
“…This is especially relevant as women with a hypertensive disorder of pregnancy give often birth to small for gestational age infants, who themselves have a higher risk of later cardiovascular disease. 40,41 Women gain on average 2 kg of weight after each pregnancy, and this is even more after a hypertensive disorder of pregnancy. 42,43 Interpregnancy weight gain is associated with a doubled risk of gestational hypertension, gestational diabetes mellitus, or preeclampsia during the next pregnancy.…”
Section: December 2012mentioning
confidence: 99%